A historian, selflessly devoted to his people - Azmukhanova, Айман (Turkic Studies Journal, 2022)
Summary of the publication. Doctor of Historical Sciences, Professor, Honorary Member of the National Academy of Sciences of the Republic of Kazakhstan, Academician of the Academy of Social Sciences of Kazakhstan, Honorary Head of the Department of al-Farabi KazNU, Director of the Republican Center for the Study of Traditional Civilizations of Central Asia Talas Omarbekuly Omarbekov (1948-2021) left a brilliant mark on the scientific and social life of the Republic. T. Omarbekov was one of the first Kazakh scientists to turn to the study of the so-called «blank page» in the national history at the beginning of independence. On the basis of previously unknownarchival documents and new methodological approaches, he managed to convey to the general public the truth about the tragic events of the period of forced collectivization and anti-Soviet uprisings. The study of the causes and consequences of the great famine of 1932-1933 in the Kazakh steppe takes a special place among his scientific works. The next direction of scientific research of T. Omarbekov were the problems related to ancient and medieval history of Kazakhstan. He made a great contribution to the research of the history of the origin of the Kazakh people, the emergence and formation of its statehood. Thanks to the enormous efforts he made when he was at the head of the historical research center «Alash», the basic monographs «History of Kazakh clans and tribes», «Ethnic history of Kazakhs», «Kazakh statehood: the history of kaganates, ulus and khanates», «Kazakh khans» and others were published. T. Omarbekov devoted the last decade of his life to the study of the ethnic history of the Turkic peoples of the Great Steppe. He headed several research projects in this direction and later was the head of the Republican Center for the Study of Traditional Civilizations of Central Asia. As a result of the fruitful work of the team of the scientific institution headed by him, he managed to publish the monograph «History of the Civilization of the Nomads of Central Asia», a collection of essays «Questions of the History of Traditional Civilization in Central Asia», a four-volume textbook «History of Kazakhstan», as well as several teaching aids. T. Omarbekov combined the qualities the qualities of a remarkable historian, a talented publicist and a public figure, which is reflected in his active cooperation with the media and numerous publications in journals. The scientist’s works were published not only in Kazakhstan, but also in foreign research journals. T. Omarbekov was an excellent mentor and managed to establish his own scientific school. Under his guidance, 7 Doctors of science and 34 Candidates of science defended their dissertations, as well as about a dozen PhDs in the field of history.